The use of the isometry of function spaces with different numbers of variables in the theory of approximation of functions - Bushev, D.M.; Abdullayev, F.G.; Kal'chuk, I.V.; Imashkyzy, M. (Carpathian Mathematical Publications, 2021)
In the work, we found integral representations for function spaces that are isometric to spaces of entire functions of exponential type, which are necessary for giving examples of equality of approximation characteristics in function spaces isometric to spaces of non-periodic functions. Sufficient conditions are obtained for the nonnegativity of the delta-like kernels used to construct isometric function spaces with various numbers of variables.